2019
DOI: 10.1097/iae.0000000000002217
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Scleral Contraction to Treat Recurrent or Persistent Macular Detachment After Previous Vitrectomy in Highly Myopic Eyes

Abstract: Posterior scleral contraction is safe and effective for recurrent and persistent macular detachment after previous vitrectomy in highly myopic eyes. The silicone oil is removed after PSC, and vision can be preserved in these refractory cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The designed amount of AL shortening before surgery was the empirical value we obtained from our previous study, which would provide a useful clue to appropriate PSC in further clinical MF treatment. 17,19 In the current study, pre-op AL of P21 was longer than 30 mm and its expected AL shortening should be more than 2.5 mm, whereas intraoperative AL shortening was less than 2 mm in actual. The insufficient AL shortening may be the core reason for unrecovery in P21 at post-op 12-month.…”
Section: Discussionmentioning
confidence: 53%
“…The designed amount of AL shortening before surgery was the empirical value we obtained from our previous study, which would provide a useful clue to appropriate PSC in further clinical MF treatment. 17,19 In the current study, pre-op AL of P21 was longer than 30 mm and its expected AL shortening should be more than 2.5 mm, whereas intraoperative AL shortening was less than 2 mm in actual. The insufficient AL shortening may be the core reason for unrecovery in P21 at post-op 12-month.…”
Section: Discussionmentioning
confidence: 53%
“…The strip material used in this study was chosen from donor sclerae and sterilised and cross-linked with genipin for increased strength and resistance to degradation, which is beneficial for the prevention of posterior scleral expansion and maintenance of long-term surgical outcomes [ 30 ]. The length and width of the strip should be pre-designed before PSR to ensure that it can completely wrap around the macula and posterior scleral staphyloma [ 5 , 11 ]. The vortex vein, optic nerve, and other important tissues should be avoided while positioning the strip to avoid disrupting the blood supply to the eye and affecting vision.…”
Section: Discussionmentioning
confidence: 99%
“…Kosei et al [ 10 ]found that eyes with PS were more likely to develop retinal vascular microfolds in the outer macular schisis, perhaps this may be related to the backward vertical force of the PS. Zhang et al [ 11 ]also considered that MTM develops due to the pulling action of posterior scleral staphyloma because the retina lacks the ductility to match the expansion of the sclera. PPV relieves the tangential and centrifugal traction forces caused by the vitreous cortex without tackling the persistently expanding posterior scleral staphyloma [ 12 , 13 ], which is the fundamental reason for its poor clinical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The strip material used in this study was chosen from donor sclerae and sterilised and cross-linked with genipin for increased strength and resistance to degradation, which is bene cial for the prevention of posterior scleral expansion and maintenance of long-term surgical outcomes 23 . The length and width of the strip should be pre-designed before PSR to ensure that it can completely wrap around the macula and posterior scleral staphyloma 5,10 . The vortex vein, optic nerve, and other important tissues should be avoided while positioning the strip to avoid disrupting the blood supply to the eye and affecting vision.…”
Section: Discussionmentioning
confidence: 99%